Cameroon Economic Update, July 2012 : Stepping Out into the World - World Bank (World Bank, Washington, DC, 2016)
With this Cameroon economic update, the World Bank is pursuing a program of short, crisp and frequent country economic reports. These economic updates provide an analysis of the trends and constraints in Cameroon's economic development. Each issue, produced bi-annually, provides an update of recent economic developments, as well as a special focus on a topical issue. The economic updates aim to share knowledge and stimulate debate among those interested in improving the economic management of Cameroon and unleashing its enormous potential. This fourth issue of the Cameroon economic update is entitled 'stepping out into the world a special focus on trade facilitation'. It reviews the challenges and opportunities related to trade facilitation in Cameroon. The coverage is not meant to be exhaustive, but puts an emphasis on particular areas that would require the country's sustained attention: a transformative trade facilitation agenda around which all stakeholders could be mobilized.